2023
DOI: 10.3390/ijms24043189
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Candidate Effectors from Magnaporthe oryzae by In Vitro Secretomic Analysis

Abstract: Magnaporthe oryzae is the causal agent of rice blast, one of the most serious diseases of rice worldwide. Secreted proteins play essential roles during a M. oryzae–rice interaction. Although much progress has been made in recent decades, it is still necessary to systematically explore M. oryzae-secreted proteins and to analyze their functions. This study employs a shotgun-based proteomic analysis to investigate the in vitro secretome of M. oryzae by spraying fungus conidia onto the PVDF membrane to mimic the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 73 publications
0
0
0
Order By: Relevance
“…At present, investigations into effectors in plant pathogenic fungi are abundant. For example, in Magnaporthe oryzae , Li et al [ 28 ] reported that of 3315 effectors, 509 proteins (15.4%) contain an SP in the N-terminus. In contrast, 2806 proteins (84.6%) do not.…”
Section: Introductionmentioning
confidence: 99%
“…At present, investigations into effectors in plant pathogenic fungi are abundant. For example, in Magnaporthe oryzae , Li et al [ 28 ] reported that of 3315 effectors, 509 proteins (15.4%) contain an SP in the N-terminus. In contrast, 2806 proteins (84.6%) do not.…”
Section: Introductionmentioning
confidence: 99%